Augmented reality navigation system for ENT : frontal sinus surgery - Goh, Tuan Siang. (2008)
This thesis explores a new medical application of Augmented Reality for Therapy System in Functional Endoscopic Sinus Surgery performed by the Ear, Nose & Throat (ENT) Department in Changi General Hospital.